AN INTRODUCTION ON FUZZY SEMI–SUBMAXIMAL SPACES AND APPLICATIONS TO MEDICAL DIAGNOSIS - D.NIRAJA,,; Dr. D.VIJAYAN,; N.MYTHILI, (The Bioscan, 2026)
Present paper studies the concept ofsemi–submaximal spacein fuzzy topological spaces. Variousproperties in fuzzy semi–submaximal spaces were investigated. To be proved that asemi-submaximal space becomes semi-nowhere dense setof topology in fuzzy.